Skills for Mining Labour Productivity Improvement. - Musingwini, M. (The Southern African Institute of Mining and Metallurgy., 2017)
Extract from Editorial: Productivity is a very relevant and important discussion point for the mining industry. It is so, given that our industry has been experiencing declining productivity in the past decade, although equipment efficiencies have been increasing. For example, according to a McKinsey study released in 2015, US mining labour productivity had declined nearly 30% since 2007, while other production sectors such as motor vehicle manufacturing had improved their productivity by nearly 180% over the same period.
President's Corner: Skills for Mining Labour Productivity Improvement.
Keywords: Mining labour; Mine workers; Productivity; Mining equipment; Mine production